Possible Effects of Beetroot Supplementation on Physical Performance Through Metabolic, Neuroendocrine, and Antioxidant Mechanisms: A Narrative Review of the Literature - Arazi, Hamid; Eghbali, Ehsan (Frontiers in Nutrition, 2021)
Athletes often seek to use dietary supplements to increase performance during exercise. Among various supplements, much attention has been paid to beetroot in recent years. Beetroot is a source of carbohydrates, fiber, protein, minerals and vitamins; also, it is a natural source of nitrate and associated with improved sports performance. Nitrates can the modification of skeletal muscle contractile proteins or calcium handling after translation. The time to reach the peak plasma nitrate is between 1 to 3 hours after consumption of a single dose of nitrate. Nitrate is metabolized by conversion to nitrite and subsequently nitric oxide. Beetroot can have various effects on athletic performance through nitric oxide. Nitric oxide is an intracellular and extracellular messenger for regulating certain cellular functions and causes vasodilation of blood vessels and increases blood flow. Nitric oxide seems to be effective in improving athletic performance by increasing oxygen, glucose and other nutrients for better muscle fueling. Nitric oxide plays the main role in anabolic hormones, modulates the release of several neurotransmitters and the major mediators of stress involved in the acute hypothalamic-pituitary-adrenal response to exercise. Beetroot is an important source of compounds such as ascorbic acid, carotenoids, phenolic acids, flavonoids, betaline and highly active phenolics such as caffeic acid, epicatechin and rutin and has high antioxidant properties. Beetroot supplement provides an important source of dietary polyphenols and due to the many health benefits. Phytochemicals of Beetroot inhibit inflammatory diseases through signaling pathways. In this research study, the mechanisms responsible for these effects were examined and the researches in this regard was reviewed.